(3JGQjN edhc Hfi YKeGf hhdGjJge HeUQs
(3ChdgG (B:s
(3jHJOF ef YUQ GdSdWGf YKeGf s
(3BNQgG (B:s
(3hdGjI eMeO Ydi HGT Ydi eUQ SfI (B1129 (3g` s
(3fSNI eUhQI Yf GdaGJjcGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B73 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdJjehQjI (B((3JGQjN (B2408) s
Keywords: (3GdJGQjNs